Catecholamine levels and activity of monoamine oxidase in some hypothalamic structures and in the pineal gland of sheep after administration of FSH - Pástorová, B; Várady, J (Physiological research, 1996)
The influence of hormonal preparations of FSH in a dose of 24 mg (480 IU) on levels of catecholamine (dopamine, norepinephrine and epinephrine) and the activity of their degradation enzyme monoamine oxidase (MAO) in the hypothalamic regions regulating the reproductive system of sheep (area preoptica, eminentia mediana, corpus mamillare) and pineal gland were investigated in the oestrous period employing radiochemical methods. The administration of FSH resulted in significant (p<0.001) increases of dopamine levels in the area preoptica and corpus mamillare of the hypothalamus of sheep as compared to control groups with synchronized oestrus. Hormonal stimulation with FSH increased the levels of hypothalamic norepinephrine in the areas studied and these differences were significant in the eminentia mediana (p<0.05) and corpus mamillare (p<0.05). Significant (p<0.001) changes in epinephrine levels were found in the corpus mamillare and area preoptica (p<0.05). Our results indicate that the administration of FSH caused the most pronounced decrease of MAO activity in corpus mamillare (p<0.001). The pineal gland reacted to the hormonal preparation by decreased levels of norepinephrine and dopamine (p<0.001) and by an increase in MAO activity (p<0.01). We suggest that FSH administration affects catecholamine levels and the activity of monoamine oxidase in the studied areas of the brain of sheep by means of a feedback mechanism.
Keywords: Dopamine; noradrenalin; Monoamine Oxidase; adrenalin; monoaminoxidasa; epifýza mozková; ovce; Hypothalamus; Follicle Stimulating Hormone; Norepinephrine; Animals; katecholaminy; zvířata; Pineal Gland; Catecholamines; Epinephrine; Sheep; hypothalamus; folikuly stimulující hormon; dopamin